Start and turn performances of elite sprinters at the 2016 European Championships in swimming - Morais, J.E. (2018)
To LEN (Ligue Européenne de Natation) and Spiideo AB for providing the videos. We would like to thank the support of the University of Beira Interior and Santander Universities (Bolsa BIPD/ICI-FCSH-Santander Universidades-UBI/2017)